Widya, Eri IMPLEMENTASI MODEL PROJECT BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS III SDN PANGGUNG LOR - Ningrum, Eri Widya; Listyarini, Ikha; Saputra, Henry Januar; Junaidi, Agus (JURNAL SINEKTIK, 2024)
This study aims to improve the cognitive learning outcomes of class III students at SDN Panggung Lor Semarang city for the 2022–2023 school year on the theme of rights and obligations through the project-based learning (PjBL) learning model. The subjects in this study were class III students at SDN Panggung Lor Semarang City, consisting of 11 female students and 17 male students. The technique of collecting data is done by giving tests and making observations. The results showed that the average class III student learning outcomes in cycle I were 68.28 and increased to 83.21 in cycle II. The percentage of students who complete the KKM has increased with each cycle. In cycle I, the percentage of students who completed the KKM was 39.29%, and then it increased in cycle II to 83.21%. These results indicate that the application of the project-based learning (PjBL) learning model can improve the cognitive learning outcomes of class III students at SDN Panggung Lor Semarang City on the theme of rights and obligations